Natural quinolone antimicrobial agents from Malaysian Rutaceous species - Mohd Hassan, Norazian; Md Taib, Nurhaya; Mohd Kamal, Laina Zarisa; Abdul Karim, Khairul Anuar; Abdul Karim, Khairul Anuar; May, Khin Soe (2011)
Various 4-oxygenated and 2-substituted 4-quinolone alkaloids with diverse structural types have been isolated and were found unique to the Rutaceae plant family. Some of these alkaloids have been demonstrated to have promising antimicrobial activity. These alkaloids possess chromophore with some structural similarities to that of the pharmacophore of the conventional 4-quinolone antimicrobial agents. Therefore it is presumed that this type of natural quinolone alkaloid could also share the same activity as the conventional agents. Three Malaysian Rutaceous species have been investigated for their natural quinolone antimicrobial agents, namely Glycosmis pentaphylla (Retz.) DC., Lunasia amara Blanco and Ruta angustifolia (L.) Pers. Bioassay-guided isolation facilitated by using bioautographic agar overlay assay against Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 35213 and Candida albicans ATCC 90028 as the indicator microbes has led to the isolation of antimicrobial 4-quinozolone alkaloid, identified as arborine, 2-quinolone namely lunidonine and 4-quinolone with the trivial name graveoline from G. pentaphylla, L. amara and R. angustifolia, respectively. These alkaloids possess promising antimicrobial activity with the minimum inhibitory concentrations (MICs) ranging between 125 µg/ml and 250 µg/ml against the tested microbes. Arborine and graveoline showed synergistic antimicrobial effect when tested in combination with ampicillin against E. coli with FIC index of 0.38 for each combination. These results show a great importance in view of finding a new structural type in overcoming the emergence of quinolone resistance against some microbes which has been a disturbing feature of microbial infections.